Roteiro cultural entre letras e pedras: lugares de memória de Erico Verissimo pelo patrimônio cultural de Cruz Alta - Dutra, Alex da Silva (2024)
The perspective of heritage education, as a constant and organized practice, opens new avenues to rethink and redefine the knowledge related to cultural heritage in educational contexts. In this sense, the present study seeks to address the need to promote heritage education in Cruz Alta, proposing the creation of the Cultural Route "Between Letters and Stones": Places of Memory of Erico Verissimo for the Cultural Heritage of Cruz Alta. The conduct of the research was developed within the scope of the Graduate Program in Cultural Heritage at UFSM, specifically in the research line of material heritage preservation and in the area of concentration in architecture and material heritage. This study aims primarily to map the places of memory related to the life and work of the writer Erico Veríssimo, highlighting them among the architectural remnants, monuments, and public spaces of Cruz Alta. Specifically, the aim is to promote knowledge and appreciation of the city's cultural heritage, emphasizing the connection with the writer Erico Verissimo through educational activities that foster civic education and a sense of belonging in new generations. To this end, a cultural itinerary is conceived that not only promotes the preservation of heritage but also keeps its memory and its connection to the place alive, in order to foster cultural tourism, stimulate heritage education, and contribute to local development. This work is justified by the aim of expanding the supply of teaching resources in heritage education and the need to value the cultural heritage of Cruz Alta, focusing on the preservation of the history and literature of Erico Verissimo and promoting greater connection with the Cruz Alta community. As for the methodology used, an exploratory qualitative approach was adopted, which included a literature review to support the study, field visits to identify and document the sites of memory, to illustrate the brochure and the points of interest to be explored in the cultural itinerary. Therefore, this study, in addition to valuing the history and culture of Cruz Alta, reveals, through the creation of the itinerary “Entre Letras e Pedras”, the cultural importance of the life and work of Erico Verissimo for the city's heritage.